THE IMPLEMENTATION OF THE RAHMATAN LIL-ALAMIN PROFILE IN FACING CHARACTER DEGRADATION IN THE SOCIETY 5.0 ERA - Lestari, Titis Wahyu Muji; Kartika, Resti Okvani; Maemonah, Maemonah (FAJAR Jurnal Pendidikan Islam, 2025)
Rahmatan lil'alamin's character education is very crucial in facing the challenges of the digital era. This article highlights how the Rahmatan Lil'alamin concept in the Merdeka curriculum creates strong and adaptive student characters. It is hoped that this curriculum can be a solution in the world of education, especially in building a generation that is not only intellectually focused, but can also pay attention to the development of morals, ethics and social skills. Information technology is currently developing rapidly, the world of education needs to filter information in depth, so that news does not match reality. In character education, the Rahmatan lil'alamin contained in the independent curriculum is very crucial in forming the habits of students who have good morals. This article discusses the integration of Rahmatan lil'alamin values ​​in the Independent Curriculum to face the challenges of the digital era. The method used in this research is a literature review study, through several research stages, namely by collecting continuous data through discussions from articles and books, as well as analyzing the data and then discussing and concluding. This article highlights the importance of character as a foundation in building individuals who are able to overcome the negative impacts of digitalization. This article also contains an in-depth analysis of strategies for implementing Rahmatan lil'alamin character values ​​in the Indonesian education system